Lecturer Performance, Self-Efficacy, and Knowledge Sharing: A Mediating Effect of Perceived Organizational Support - Hermawan, Novan; Trisninawati, Trisninawati; Gunarto, Muji (Economic Education Analysis Journal, 2025)
This study uses perceived organizational support (POS) as a mediating variable in a private institution to investigate how self-efficacy and knowledge sharing affect professor performance.  240 lecturers from 16 private universities in Palembang City were surveyed as part of this study's quantitative technique, which was chosen by stratified random sampling.  Through LISREL, structural equation modeling, or SEM, was used to analyze the data.  The results show that while self-efficacy has no direct impact on lecturer performance, it has a favorable and significant impact on POS.  On the other hand, it has been demonstrated that information exchange considerably and favorably affects lecturer performance, but not perceived organizational support (POS). Concurrently, it has been demonstrated that POS mediates the relationship between self-efficacy and lecturer performance and considerably enhances lecturer performance; however, it does not mediate the relationship between performance and knowledge sharing.  These results validate the importance of organizational support in maximizing individual contributions, especially in boosting knowledge-sharing behavior and self-efficacy.  According to this study, private institutions should enhance organizational support systems that can boost self-esteem and promote a knowledge-sharing culture in order to maximize the effectiveness of the Tri Dharma of Higher Education.